Rancang Bangun Emergency Box Berbasis Solar Panel di Lingkungan Pondok Pesantren Raudlatul Ulum Kalisat Jember - Aziz, As'ad Shidqy; Widyartono, Mahendra; Wardani, Ayusta Lukita; Rahmadian, Reza; Hermawan, Aditya Chandra; Rahmatullah, Daeng; Amaliah, Fithrotul Irda (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
This community service activity aims to design and implement a solar panel-based Emergency Box as a learning medium and emergency power supply solution at the Raudlatul Ulum Islamic Boarding School, Kalisat, Jember. This activity was motivated by limited electrical facilities and minimal learning practice facilities within the Islamic boarding school environment. The implementation method included literature study, needs analysis, system design, tool assembly, and outreach and mentoring activities for teachers and students. The results of the activity showed that the designed Emergency Box was able to function optimally as an alternative power source for lighting and charging electronic devices. Through training and mentoring, teachers and students gained an understanding of the working principles of solar energy as well as technical skills in operating and maintaining the device. This activity is expected to improve the quality of practice-based learning and raise awareness of the importance of using renewable energy in the Islamic boarding school environment